Antimicrobial Properties of Fucus Vesiculosus and Porphyra Dioica Collected From the Irish Coast. - Lenka Jindrichova; Annabel Higgins Hoare; Helen Hughes (SURE Journal: (Science Undergraduate Research Experience Journal))
Various types of algae play an important role in entire ecosystem and has potential role in the continuous search for biologically active compounds with miscellaneous activities, such as antioxidant, antiviral and antimicrobial. The objective of this study was to study the antimicrobial properties of two diverse seaweeds, Fucus vesiculosus and Porphyra dioca. Antimicrobial compounds from both seaweeds could find potential future use in medical or food industries. Water content analysis was performed on both seaweeds and it was determined that high water content around 80% was apparent for both seaweeds, with higher consistency of water content found for Porphyra dioica compared to Fucus vesiculosus. Extraction of active metabolites was performed in diethyl ether, methanol and water; solvents with various polarities at a concentration of 1/100 w/v. Only Porphyra dioica was additionally extracted in ethyl acetate and a methanol:water mixture at concentrations 1/100 w/v and 1/30 w/v, respectively. The seaweed crude extracts were tested against one active pathogenic clinical strain of Methicillin Resistant Staphylococcus aureus (MRSA) WIT-676 obtained from University Hospital Waterford. The effect of various extracts concentrations 1/40, 1/60, 1/80 and 1/100 w/v in methanol was examined using extracts of Fucus vesiculosus followed by antimicrobial screening against the same pathogen to determine the optimal concentration of active metabolites in relation to the screening and which would then require further separation. The highest antimicrobial activity from an extract of Porphyra dioica was found in ethyl acetate and the solvent mixture methanol;water (1:1) compared with Fucus vesiculosus, which exhibited the highest antimicrobial activity in water and methanol extracts. Further analysis for separation of all crude extracts would be required with potential use of those extract in medical area.